Įsigijimo ciklo auditas statybinėse įmonėse - Pečiūra, Vilmantas (Journal of Civil Engineering and Management, 1998)
Audit of acquisition cycle in construction enterprisesAuditing is a systematic process of objectively obtaining and evaluating evidence regarding assertions about economic actions and events to ascertain the degree of correspondence between the assertions and established criteria and communicating the results to interested users. The purpose of auditing is to add credibility to financial statements by providing independent, objective and proffessional opinion on audited financial statements. One effective way to perform an audit is to classify transactions into “cycles” of related activities. An acquisition cycle is important for construction enterprises. The main activities of the acquisition cycle is: 1) purchase requisition, 2) authorized acquisition of materials, 3) receive of materials, 4) transaction recording in accounting, 5) bill payment authorization, 6) cash disbursement. Auditors should test financial statements assertions – existence, completeness, rights and obligations, valuation, and presentation and disclosure – embodied in the acquisition cycle. Auditors should evaluate the control risk of the acquisition cycle. If the control risk is low, the number of substantive audit procedures can be reduced. Some construction enterprises centralises acquisition function in a separate department. Centralisation is helpful in the following way: 1. Purchasing effectiveness is increased. 2. The department managers opportunity to favour certain suppliers is eliminated. 3. The segregation of acquisition, custody and accounting functions diminishes fraud possibilities. 4. The control function is centralised in one department.Information about control structure could be obtained by the questionnaire or by reperformance of control procedures. Substantive audit tests could be classified into two categories: analitycal tests and detail test of account balances and transaction classes. When considering assertions and obtaining evidence about accounts payable and other liabilities, auditors must put emphasis on the completeness and obligations assertions. The enterprises typically are less concerned about timely recording of expenses and liabilities than they are about timely recording of revenues and assets. This would work in opposite way if the main purpose of the enterprise is to hide taxes. Search for unrecorded liabilities is expanded into other fields of auditing – they could be discovered auditing other cycles. Auditor tests receiving reports, supplier's invoices, cash disbursements maid after year end, scans various documents for exceptional amounts. Mistakes should be pointed out in the working papers. Confirmations could also be used for the completeness assertion auditing. Vouching procedure is widely used for evaluation assertion. Liabilities account balances are checked with supporting documentation. Auditors should test proper presentation and disclosure of liabilities. Auditors are mainly concerned that accounts payable contain only amounts associated with the acquisition of materials.Article in Lithuanian.First Published Online: 26 Jul 2012